2000
DOI: 10.1159/000029164
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Delusional Beliefs in Schizophrenic and Unipolar Mood Disorders: A Comparative Study

Abstract: We assessed comparatively 13 clinical features of delusions in a sample of 132 deluded inpatients of both sexes with schizophrenic (n = 89) or unipolar mood disorders (n = 43). Patients with schizophrenic disorders exhibited higher levels of severity than those with unipolar depression with respect to the features of vagueness-illogicality, bizarreness, systematization, conviction, duration and affective incongruence, whereas the reverse held true with respect to the feature of emotional impact. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This pattern of association reflects the underlying diagnostic category of psychotic depression. These results are in line with a study among younger adult patients with either schizophrenia or psychotic depression in Athens …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This pattern of association reflects the underlying diagnostic category of psychotic depression. These results are in line with a study among younger adult patients with either schizophrenia or psychotic depression in Athens …”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with a study among younger adult patients with either schizophrenia or psychotic depression in Athens. 25 A limitation of the current study is that the participation rate of 63% remains behind what would have been achieved with an entirely consecutive sample. No data were collected on the number of patients who refused to be interviewed or who were not identified by their clinicians as meeting the criteria.…”
Section: Delusional Characteristicsmentioning
confidence: 85%
“…To date there have been a limited number of studies investigating differences between delusions in schizophrenia compared with delusions in affective psychosis and these have yielded conflicting evidence. Oulis et al (2000) compared delusional beliefs in schizophrenia and unipolar mood disorders using a 13item scale and found that schizophrenic delusions were more illogical, bizarre, systematised, held with greater conviction and for a longer duration with greater affective incongruence while those in psychotic depressives were subject to greater emotional impact. Other studies however, suggested that delusions have similar characteristics across diagnostic categories.…”
Section: Delusions and Affectmentioning
confidence: 99%